2017
DOI: 10.3389/fnagi.2017.00194
|View full text |Cite
|
Sign up to set email alerts
|

Aging Microglia—Phenotypes, Functions and Implications for Age-Related Neurodegenerative Diseases

Abstract: Aging of the central nervous system (CNS) is one of the major risk factors for the development of neurodegenerative pathologies such as Parkinson’s disease (PD) and Alzheimer’s disease (AD). The molecular mechanisms underlying the onset of AD and especially PD are not well understood. However, neuroinflammatory responses mediated by microglia as the resident immune cells of the CNS have been reported for both diseases. The unique nature and developmental origin of microglia causing microglial self-renewal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
174
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(180 citation statements)
references
References 113 publications
6
174
0
Order By: Relevance
“…The genomic signature of aged microglia has been of great interest since the advent of next generation sequencing technologies. Unfortunately attempts to characterise them have yielded varied and often conflicting results with no clear and consistent specific genetic or protein markers for aged microglia emerging (Crotti and Ransohoff ; Wes et al ; Spittau ; Olah et al ). The aged microglia in the mouse retina exhibited significant changes in genes controlling inflammation including the NF‐κB signalling pathway and up‐regulated complement genes C3 and complement factor B (Ma et al ).…”
Section: Dystrophic and Senescent Microgliamentioning
confidence: 99%
See 1 more Smart Citation
“…The genomic signature of aged microglia has been of great interest since the advent of next generation sequencing technologies. Unfortunately attempts to characterise them have yielded varied and often conflicting results with no clear and consistent specific genetic or protein markers for aged microglia emerging (Crotti and Ransohoff ; Wes et al ; Spittau ; Olah et al ). The aged microglia in the mouse retina exhibited significant changes in genes controlling inflammation including the NF‐κB signalling pathway and up‐regulated complement genes C3 and complement factor B (Ma et al ).…”
Section: Dystrophic and Senescent Microgliamentioning
confidence: 99%
“…However, such studies have largely focussed on abnormal glia behavior such as activation of microglia or the formation of astrocyte scars and the secretion of pro‐inflammatory cytokines (Liddelow ). However, there is increasing evidence that glia cells undergo an aging process and this may also impact neurodegenerative disease progression (Spittau ; Holtzman and Ulrich ; Cohen and Torres ). These glial cells can be described as either senescent or dystrophic (Streit et al ).…”
mentioning
confidence: 99%
“…Microglia shows age‐dependent cellular dystrophy and become senescent . This senescence in microglia leads to functional changes that may be responsible for an age‐dependent increase of microglia‐mediated neuroinflammatory response, which can also damage aged neurons . Various studies have investigated age‐dependent changes in the number of microglia in different brain regions across different species.…”
Section: Microglial Sex Differences During Agingmentioning
confidence: 99%
“…The pro‐inflammatory cytokines, IL‐1β, TNFα, and IL‐6, were all increased after LPS challenge in aged microglia . Other signs of increased age‐dependent microglia are the expression of immune cell markers such as MHCII, macrophage marker CD68, and Toll‐like receptors (TLRs), which all play a role in the inflammatory response after CNS injury . TLRs have been implicated in the role of both the detrimental and protective roles after ischemia and are involved in the activation of microglia poststroke .…”
Section: Microglial Sex Differences During Agingmentioning
confidence: 99%
“…It is crucial in clearing debris, apoptotic/ necrotic cells, or products from necrotic cells, infiltration of infectious agents, mediating the brain's inflammatory and repair response to traumatic injury, stroke, or neurodegeneration [79]. It was suggested that age-dependent and senescence-driven impairments of microglia functions and responses play essential roles during onset and progression of neurodegenerative diseases as AD and PD, in which molecular changes on microglia senescence are similar [80]. The unique nature and developmental origin of microglia causing microglial selfrenewal and telomere shortening led to the hypothesis that these CNS-specific innate immune cells become senescent [81].…”
Section: Sex Hormones In Neurodegenerative Processes and Diseases 132mentioning
confidence: 99%